A Case Study Of The Factors Influencing Argumentative Writing Activities Via Whatsapp Among Low Proficiency Esl University Students - Haron, Haeza (2023)
This case study examines low-proficiency university students’ views of three learning factors that influence ESL argumentative writing skills. This case study focuses on three factors: mobile technology via WhatsApp, peer interaction and teacher’s role to examine the low proficiency students at the university level view these factors as important learning criteria that can develop and support their ESL argumentative writing in answering the research questions.